Разложите на множители , 2x^3-14x^2+18x y^6-2y^4+3y^2 a(x-2y)-ab(x-2y) x(a^2-ab)+y(ab-a^2)

Шлюбка Шлюбка    3   30.05.2019 00:40    0

Ответы
Давид1111david Давид1111david  29.06.2020 15:55
1).  2х³-14х²+18х=2х*(х²-7х+6), где х²-7х+6 раскладываем на множители (D=в²-4ас=49-24=25 х1 = (7-5)/2=1;  х2=(7+5)/2=6) получаем следующее: 2х*(х-1)*(х+6)
2).  a(x-2y)-ab(x-2y)= (х-2у)*(а-ав)= (х-2у)*а*(1-в)
3).  x(a²-ab)+y(ab-a²)=а²х-авх-аву-а²у= а² * (х-у)-ав*(х-у)= (х-у)*(а²-ав)= (х-у)* а * (а-в)
ПОКАЗАТЬ ОТВЕТЫ